Anatomia da soldadura do enxerto de garagem, no topo, em abacateiro (Persea americana Mill) e mangueira (Mangifera indica L) - Shimoya, C; J Gomide, C; V R Pinheiro, R (Revista Ceres, 2025)
Grafting success in avocado (Persea americana L.) and mango (Mangifera indica L.) seedlingsthree months oldis quite similar. Three groups can be recognized: a) grafting is set, but the scion does not develop and sometimes the stock shoots off; b) the scion dies and the stock shoots off vigorously; c) the scion dies and no shoots develop from the stock. There is an intense callus formation, starting from two regions, cambial layer and pith parenchyma, the latter being predominant in mango. The initial histological connection is made through the callus parenchyma.